Analytical evaluation of direct bicarbonate measurement with the new gem premier chemstat in hemodialysis patients. (1st September 2021) - Balboni, Fiamma; Terreni, Alessandro; Gallo, Marco; Guzzi, Francesco; Caparrini, Chiara; Burbui, Stefania; Vezzosi, Marco; Galora, Silvia; Lori, Giulia; Lippi, Giuseppe
Abstract: GEM Premier ChemSTAT is a whole-blood analyzer designed for providing a rapid basic metabolic panel, inclusive of creatinine and blood urea nitrogen, with the unique characteristic of providing measured bicarbonate (HCO3 – ) levels. The aim of this work was to evaluate the clinical performance of HCO3 – assessment with this analyser in a real-life hemodialysis setting. Imprecision was calculated at different HCO3 – levels, along with assay comparison with Gem Premier 4000 analysers. GEM Premier ChemSTAT displayed an imprecision and a bias (in comparison to GEM Premier 4000) for HCO3 – of 0.4% and 37.3% at 20.8 mmol/L, 1.2% and 25.6% at 16.4 mmol/L, and 2.1% and 11.6% at 11.5 mmol/L, respectively, using three levels of HCO3 – quality control sample ChemSTAT System Evaluator. At direct comparison with the GEM Premier 4000 in the hemodialysis setting, Bland–Altman analysis of HCO3 – levels evidenced a bias ( µ ) of −4.9 (95% CI, −5.2 to −4.7) mmol/L. Such difference was attenuated by recalculating the GEM ChemSTAT expected HCO3 – values from pH and pCO2 using the Henderson Hasselbach equation, µ =–0.07 (95%CI, −0.19 to 0.05) mmol/L ( p  = .24). In conclusion, our results show a remarkable difference between the HCO3 – values reported by GEM ChemSTAT or GEM 4000. New reference values for GEM ChemSTAT HCO3 – shall hence be defined according to our findings. We suggest that further investigation and a re-evaluation of the reference range should be made before extending the clinical use of this device.